In Silico, In Vitro, and In Vivo Investigations of Anticancer Properties of a Novel Platinum (II) Complex and Its PLGA Encapsulated Form - Zahra Shabaninejad; Mahdiyar Dehshiri; Sayed Mostafa Modarres Mousavi; Maryam Nikkhah; Sadegh Shirian; Sajad Moradi; S. Masoud Nabavizadeh (Bioinorganic Chemistry and Applications)
In recent years, the development of multinuclear platinum complexes has introduced a new era in platinum-based chemotherapy, offering improved cytotoxicity and the ability to overcome resistance. However, these complexes still face challenges related to water solubility, biodistribution, and targeted delivery. This study provides a comprehensive investigation of a novel platinum (II) complex, [Pt2(μ-bpy-2H) (Me)2(dmso)2] (C1), focusing on its DNA binding ability and anticancer activity. Computational and experimental approaches revealed that C1 binding to guanine bases and involvement of intercalative interactions. C1 exhibited cytotoxicity in both cisplatin sensitive and resistant cancer cell lines. To enhance the pharmacokinetic and pharmacodynamic properties of C1, it was encapsulated using poly (D, L-lactic-co-glycolic acid) (PLGA). Molecular dynamic simulations predicted the formation of stable C1/PLGA complexes during the early stages of simulation. Encapsulated C1 showed superior antitumor activity with significantly reduced side effects in tumor-bearing mouse models. In conclusion, this study highlights the novel platinum (II) complex C1 as a promising anticancer agent, especially when paired with PLGA encapsulation to improve its effectiveness and reduce side effects.